Vernetzte Islamfeindlichkeit Die transatlantische Bewegung gegen »Islamisierung«. Events - Organisationen - Medien - Wäckerlig, Oliver (Religionswissenschaft, 2019)
With the slogan of "Islamization" different social currents mobilize their followers. It also serves the fight against liberal democracies with their social pluralism. In the intra-societal cultural struggle, apocalyptic down and downfall scenarios call for fundamental change. Oliver Wäckerlig's network analysis traces a transatlantic Islamophobic movement with its transitions to the middle of society and shows an organizational continuity from anti-communism to Islamophobia. "Islam experts" stand in various roles at the hinges of the network and connect actors, organizations and media.